The Effect Of Product Quality, Price, And Promotion On Purchase Decision At Dahari Store Kota Pangkal Pinang (Case Study on Customers in The City of Pangkal Pinang 2022) - Adrian Radiansyah; Aditya Dwinanda (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of product quality, price, promotion on purchasing decisions at Dahari Stores, Pangkalpinang City. This research is a quantitative research, so the data collection that will be used in the research is done by using a questionnaire that will be filled out directly by the respondent. This study uses multiple linear regression analysis with the result that it is known that the variables of product quality, price, promotion on purchasing decisions at Dahari Stores, Pangkalpinang City. The results of the F test show that F_count is 39.011 > F_table 2.70 with a significance level of 0.000 < 0.05. This shows that the independent variables, namely product quality, price, and promotion together are proven to have a significant influence on purchasing decisions. The t-test aims to show how far the influence of one independent variable or independent variable (X) individually in explaining the variation of the dependent variable or the dependent variable (Y) is. The coefficient of determination (R Square) is 0.560, which means that 56% of the independent variables are able to explain the effect on the dependent variable, while 44% is influenced by other independent variables not included in the study.